The Treatment of Hospital Wasterwater Electrocoagulation Using Iron Electrodes: Analysis by Response Surface Methodology - M. Yusuf, Darmadi; Lubis,, Mirna Rahmah; Adisalamun, Adisalamun (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2019)
Hospital wastewater basically contains organic materials and inorganic materials. Levels of these materials can be determined by testing of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Dissolved Solid (TDS), and Total Suspended Solid (TSS). The hospital wastewater treatment proposed in this research is the electrocoagulation treatment using electrodes Fe-Fe and uses the response surface method for optimizing the response variable. Referring to this resea rch, the result shows that the relationship between the process variables and the TSS is significantly influential. As the contact time (15, 30, and 45 minutes) is longer and the voltage (6, 9, and 12 volts) is higher, the percentage reductions of TSS increase. However, the electrolyte solution (01 M) has little influence/significance to a response variable of TSS. The highest percentage of TSS reduction is at the contact time 30 minutes and 12 volts, which declined at contact time 45 minutes. The model recommended is a quadratic form with a low error less than 1.6%. In such a way, the optimum condition is at contact time 36 minutes, voltage 12 volts, and the electrolyte (NaCl) concentration 0.1 M. The reduction percentage is TSS 72.45%.